Creative decision making : using positive uncertainty - Gelatt, H.B. (Crisp Pub. Menlo ParkUS, 1991)
Presents positive uncertainty (PU), a new process for decision making and future planning. Explains the challenges facing today's decision makers and introduces PU's creative but paradoxical principles which focus on combining logic and intituition in decision making.